Copper‐Catalyzed Synthesis of O/N‐Alkyl S‐Phenyl Phenylcarbamothioates: An Odorless and Chemo‐selective Chan–Lam Reaction to Construct C−S Bond - Wu, Yu−Xi; Wang, Xi; Li, Jing‐Hang; Xiao, Hua‐Qing; Dong, Zhi‐Bing (European journal of organic chemistry, 2022)
A simple and efficient synthetic method to C−S bonds was established based on the Chan–Lam reaction. A series of O/N‐alkyl S‐phenyl phenylcarbamothioates were obtained in good yields by using odorless O/N‐alkyl phenylthiocarbamates as sulfur sources and commercially available phenylboronic acids as substrates catalyzed by Cu(OAc)2. This methodology features simple performance, odorless sulfur source, easily available starting material, good functional group tolerance, and high chemo‐selectivity to construct C−S bonds, thereby providing an alternative way to the synthesis of potentially bioactive compounds. A series of O/N‐alkyl S‐phenyl phenylcarbamothioates were obtained smoothly by using odorless organosulfur sources and commercially available phenylboronic acids through a Chan–Lam reaction. The methodology features simple performance, odorless organosulfur source, selective C−S bond formation, and a good functional group tolerance.